Authorities and competence of local government bodies in the field of guardianship and care of adults in Ukraine - Tytykalo, Roman (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
This article describes the powers and competence of local self-government bodies in the field of guardianship and care of adults in Ukraine. The existing legislative regulation of the organization and activity of local self-government bodies as bodies of guardianship does not fully resolve the issue of determining the legal status of such bodies in general and their socio-economic role in the researched area in particular. Guardianship and guardianship bodies remain impersonal and undefined in the structure of local state authorities and local self-government bodies, which is a significant obstacle on the way to achieving the goal of guardianship and guardianship. The legislative basis and practical organization of the activities of local self-government bodies during their exercise of powers of guardianship and care over adults are characterized. Relevant duties have been defined and analyzed, which, based on the results of the study, are proposed to be classified into three main groups: 1) to ensure, protect and defend the rights and legitimate interests of adults who need guardianship or care; 2) from the control and supervision of the activities of other than the guardianship and guardianship bodies of subjects of guardianship and guardianship (guardians, custodians and special institutions); 3) from control and supervision of property preservation and property management of persons under guardianship and care). One of the economic components of the role of local self-government bodies in the person of their executive bodies in the context of the issue of guardianship and care of adult incapacitated persons and persons whose legal capacity is limited is the exercise of relevant powers by employees of these bodies at the expense of salary funds without additional payments purely for the management of guardianship matters and care of adults. Based on the content of the powers of the guardianship and guardianship bodies, these bodies, in the manner determined by them, must also control the guardianship and guardianship of adults by special institutions.